METODE DAKWAH MENURUT AL-QURAN - Aliasan Aliasan (Wardah, 2011)
Eventhough the material or the message that will be delivered is the great one, if it is not followed by the suitable method, it will be useless. Method is the important one. The message can be refused by the receiver, even also can make  the aim of the material that will be delivered unclear. Expert call it by ‘the method is message’. Therefore, the accurateness of the messenger in deciding and considering  the method that will be used in delivering the message is very influencial for the success of implementing ‘Islam’ in society.